Ecto‐5′‐nucleotidase (CD73) is a potential target of hepatocellular carcinoma. Issue 7 (11th November 2018) - Shali, Shalaimaiti; Yu, Jiangang; Zhang, Xin; Wang, Xue; Jin, Youping; Su, Minsheng; Liao, Xiaohong; Yu, Jerry; Zhi, Xiuling; Zhou, Ping
Abstract: High expression of ecto‐5′‐nucleotidase (CD73) has been reported in a number of epithelium origin malignancies. Here, we hypothesize that CD73 promotes hepatocellular carcinoma (HCC) growth and metastasis and that the effect is mediated by epithelial growth factor receptor (EGFR). HCC cells with different malignancies and Tissue microarrays of the tumor and peritumoral liver tissues from 30 independent patients were used to examine CD73 and EGFR expression. Then, MTT and Ki67 detection, together with cell adhesion, invasion, and migration assays were used to evaluate the effects of CD73 on cell growth and metastasis. The expression of EGFR in HCC cells was also tested after suppressing or overexpressing CD73. Lastly, tumor tissues from nude mice, which had been injected subcutaneously with HCC cells, were transplanted subcutaneously into CD73 −/− and wild‐type (WT) C57 mice. CD73 expression was higher in HCC cells with greater metastatic potentials and tumor tissues compared with low metastatic cells and peritumor tissues. CD73 and EGFR were coexpressed and positively correlated in tumor and peritumor liver tissues in HCC tissue microarrays. Up‐regulationof CD73 by plasmid transfection or by pharmacological agents promoted EGFR expression in HCC cells, whereas suppression of CD73 inhibited these effects. The growth of transplanted tumor tissues was dramatically slower in CD73 −/− mice than in WT type mice in the in vivo experiments. CD73 promotes HCC growth and metastasis and upregulated the expression of EGFR in HCC. Thus, CD73 and EGFR are potential targets in the treatment of HCC. Abstract : CD73 promotes hepatocellular carcinoma (HCC) growth and metastasis, in vitro and in vivo, mediated by epithelial growth factor receptor (EGFR).